Ways to improve tax risk assessment and management mechanisms in the control of taxpayers in the examination of counterparties - Tadjiyev Abdurauf Abduvoxid o'g'li (Genius Journals, 2024)
The article states that tax authorities can improve their ability to detect possible tax evasion, ensure fair and equitable taxation, and ultimately contribute to the overall efficiency of the tax system by improving the practice of monitoring counterparties and taxpayers' activities. In the conditions of the new Uzbekistan, along with the measures aimed at increasing the volume of production based on the stimulation of taxpayers' activities, a wide emphasis is placed on the effective implementation of practical measures aimed at reducing the state budget losses through the optimal assessment of tax risks arising in them. In addition, the tax system of our republic is explained by the fact that, on the one hand, it can be used in the implementation of special scientific researches and in the creation of scientific and educational literature related to the assessment and management of tax risks related to the tax payers and the resulting tax risks related to the state budget. One of the characteristics of economic risks is that they are based on risk. Risks always cross interests, which do not correspond to the main interests of those who conduct economic activity. In addition, another sign that reveals the essence of economic risks is that it is always unstable, in this respect it is necessary to evaluate it, and this is its important sign. Economic risks make it difficult for those who carry out economic activities (legal entities and individuals) to achieve their goals, which indicates its extreme complexity, therefore, it evaluates the optimality of their economic decisions, which represent important signs of economic risk
Keywords: tax; budget policy; budget